Innovations in Environmental Risk Assessment and Life Cycle Analysis for Ecotourism Sustainability - Talukder, Mohammad Badruddoza (Fronteira: Journal of Social, Technological and Environmental Science, 2026)
The objective of this research is to develop an integrated environmental framework that combines Environmental Risk Assessment (ERA) and Life Cycle Analysis (LCA) to improve ecotourism sustainability. It aims at bridging theoretical and practical approaches by incorporating digitalization, data-driven decision-making, and collaborative governance in the context of ecotourism. This study is qualitative and thematic, merging a research design based on secondary data from previous literature. The paper presents five merging themes, interconnected dimensions, digitalization of ERA, integration of LCA, data-driven decision support and predictive analysis, governance, collaboration and policy alignment, and socio-environmental and economic co-benefits, and relates them to the significant theoretical developments, such as the evolution of the Smart Ecotourism Sustainability Theory. The results show that environmental assessment tools, technological innovation, and policymakers’ collaboration reinforce sustainable ecotourism management. The suggested framework offers destination managers, policymakers, and tourism operators a systematic framework to evaluate and improve ecotourism sustainability. This paper adds value to the existing body of literature on ecotourism sustainability by providing an in-depth synthesis of ERA and LCA that demonstrates how their combination contributes to theoretical knowledge and practical implementation. All data used in this study were derived from publicly available secondary sources, and no human participants or sensitive personal information were involved. The research develops a new interdisciplinary framework that facilitates adaptive, technology-based, and governance-focused solutions for sustainable ecotourism development.